Retinal vessel density using optical coherence tomography angiography as a potential biomarker in patients with cerebral small vessel disease - Nevine El Nahas; Tamer Roushdy; Mona Wahid el din; Mona Abdellatif; Sara Gaber; Weam Ebeid; Hossam Shokri (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background Optical coherence tomography angiography (OCTA) is a quick, noninvasive modality that visualizes retinal microvasculature. The retina is known to be the mirror of the brain, thus it is pertinent to employ OCTA to study covert cerebral small vessel disease (CSVD). Methods This is an observational case–control study of 40 patients with CSVD and 20 healthy controls. Mini-mental state examination (MMSE) was performed for all subjects, to exclude dementia. Fazekas grading and SVD score were determined by MRI. OCTA was performed for both groups and included various parameters of superficial and deep retinal capillary plexus density, macular, foveal and ganglion cell complex thickness, in addition to optic nerve head scans. Results Seventy percent of the patients had a low SVD score (1). Case group had significantly lower scores on most parameters of retinal capillary plexus density and macular thickness p < 0.05. Impairment of OCTA parameters was associated with higher Fazekas and SVD scores. Conclusion OCTA is a handy, noninvasive tool that enables the visualization of diminished retinal microvascular density in cases of early CSVD. It can serve as a screening tool for identifying vulnerable populations, facilitating early management for CSVD.